Implementasi Strategi Flipped Classroom Dalam Pembelajaran Matematika Terhadap Kemampuan Kognitif Ditinjau Dari Minat Belajar Siswa SMA Negeri 1 Surakarta - Widayati, Farida Esti, Prof. Dr. Budi Murtiyasa, M.Kom (2014)
The purpose of this research is to analyze : (1) the influence of the use of flipped classroom strategy to student's cognitive abilities, (2) the influence of student's learning interest to cognitive abilities, (3) the interaction between the use of flipped classroom strategy and student's learning interest to cognitive abilities. The populations are all students o grade XI IPA of 2013/2014 academic year in SMA Negeri 1 Surakarta. Sample taken in this research as many as two classes, consist of XI IPA 2 as experiment class with 32 students and XI IPA 1 as control class with 32 students. The sampling technique used in this research is cluster random sampling. Data collection method used are questionnaire method, method of test and documentation method. Data analysis techniques use two ways analysis of variance with unequal cells, a prerequisite test used the Liliefors method to normality test and the Bartlett method to homogeneity test. From the analysis of data with 5% of significant level, it is satisfied that : (1) there is no influence of the use of flipped classroom strategy to student's cognitive abilities with FA = 3,801, (2 ) there is no influence of student's learning interest to cognitive abilities with FB = 2,242, and (3) there is no interaction between the use of flipped classroom strategy and student's learning interest to cognitive abilities with FAB = 0,098.